Power Matrix of Spherical and Conical Wavestar Geometry with Linear and Circular Arrangement - Sara Jahangiri; Hassan Ghassemi; Hamid Reza Ghafari3; Parviz Ghadimi (International Journal of Marine Engineering Innovation and Research, 2022)
This article investigated two different arrays of Wavestar wave energy converter (WEC) with two spherical and conical WEC geometry. The boundary element method and radiation/diffraction theory have been used to evaluate the absorbed power of the Wavestar WECs under different wave heights and periods. For validation of numerical analysis, the heave position and velocity for with and without damping coefficient compare with experimental data. Single Wavestar with spherical and conical geometry under different wave periods were investigated and then two linear and circular arrays for both considering geometries compared with each other. The result shows better performance of a circular array than a linear array for all WECs. Absorbed power by the conical geometry is bigger than the spherical geometry. Besides, the maximum power is belonging to the wave period of 6s and 7s for a circular array while in a linear array the maximum power shift to wave periods of 7s and 8s.